1990
DOI: 10.1159/000293316
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture before Delivery: Effect on Pain Perception and the Need for Analgesics

Abstract: Pain experience and the amount of analgesics needed during labor were studied in 32 primiparous women who had received repeated treatment with acupuncture (AP) during the month prior to term and in 16 nontreated primiparous women. The women’s psychological profiles were evaluated by a psychiatric interview at week 38 of pregnancy. Treatment with AP did not reduce the need for analgesics in labor. During labor, all women experienced successively rising pain irrespective of whether or not they had been treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Use of Numeric Rating Scale (NRS), instead of the VAS, was based upon negative experiences, where the parturients showed irritation concerning the slide rule. The VAS is a validated instrument in assessing pain 19 and has been used in trials concerning labour pain 20,21 as well as acupuncture treatment 4,8,16 . The NRS is found to be well correlated with the VAS 22 -24 .…”
Section: Acupuncture Treatment During Labour-a Randomised Controlled mentioning
confidence: 99%
See 2 more Smart Citations
“…Use of Numeric Rating Scale (NRS), instead of the VAS, was based upon negative experiences, where the parturients showed irritation concerning the slide rule. The VAS is a validated instrument in assessing pain 19 and has been used in trials concerning labour pain 20,21 as well as acupuncture treatment 4,8,16 . The NRS is found to be well correlated with the VAS 22 -24 .…”
Section: Acupuncture Treatment During Labour-a Randomised Controlled mentioning
confidence: 99%
“…A literature review conducted in 1998-1999 (A Ramnerö, unpublished data) was unable to verify that any randomised controlled trials concerning the effectiveness of acupuncture during labour had been conducted. An analgesic effect of acupuncture treatment during labour is reported in some studies 3,5,6 , others find poor analgesic effect of the treatment 2,4 . These studies differ widely in methods, localisation and amount of acupuncture points.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Acupuncture has been widely used for killing pain in clinical practice, involving the management of headache, sore throat, hypochondria pain, stomachache, lower abdomen pain, renal colic, acute lumbar sprain, etc [4,5] . It is also reported that acupuncture can effectively attenuate anxiety and hypertension before surgery, and muscular pain after surgery [6][7][8] , and also help reduce labor pain [9,10] . There are also some reports about acupuncture for treating sciatica [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Although ton, et al, 1997). Although the findings in this study are limited to the heavier LBW infants, this piece of research related to the use of acupuncture for pain relief during labor is controversial and has resulted in mixed information is valuable to the parents of premature infants in that the parents could request specialized services results (Lyrenas, et al, 1990), Tempfer's study provides strong evidence that acupuncture has a role in reducing for their child.…”
mentioning
confidence: 94%